128k views
1 vote
Please help! ASAP!!!

Please help! ASAP!!!-example-1

1 Answer

3 votes

Answer:

Final answer is
-112\cdot√(2)a^5.

Explanation:

Given expression is
(a-√(2))^8.

Now we need to find the fourth term of the given expression
(a-√(2))^8. So apply the nth term formula using binomial expansion.

exponent n=8

4th term means we use r=4-1=3

x=2,
y=-√(2)

rth term in expansion of
(x+y)^n is given by formula:


(n!)/(\left(n-r\right)!\cdot r!)x^(\left(n-r\right))\cdot y^r


=(8!)/(\left(8-3\right)!\cdot3!)\cdot a^(\left(8-3\right))\cdot\left(-√(2)\right)^3


=(8!)/(5!\cdot3!)\cdot a^5\cdot\left(-2√(2)\right)


=(40320)/(120\cdot6)\cdot a^5\cdot\left(-2√(2)\right)


=56\cdot a^5\cdot\left(-2√(2)\right)


=-112a^5\cdot√(2)


=-112\cdot√(2)a^5

Hence final answer is
-112\cdot√(2)a^5.

User Author
by
5.1k points